Childhood and Nation Interdisciplinary Engagements - Millei, Zsuzsanna; Imre, Robert (Critical Cultural Studies of Childhood, 2016)
Childhood and Nation explores the historical and manifold current relations between nation and childhood. Millei and Imre bring together an international and interdisciplinary group of scholars to address many pressing questions of today. The analytical incisions created by nation and childhood bring answers to the following questions: How do national agendas related to economic, social and political problems exploit children and tighten their regulation? How do representations of nations take advantage of ideals of childhood? Why do nations look to children and search for those characteristics of childhood that help them solve environmental and humanitarian issues? The book offers a fresh look at the theme of nation and childhood by offering multiple methodologies from fields including education, policy studies, political science, sociology, anthropology, literature, and psychology.